New Zealand National GDM Guidelines: an alternative view of some good practice points. (February 2015) - Rowan, Janet; Allen, Helen; Budden, Astrid; Elder, Rose; Farrant, Matthew; Hughes, Ruth; Ivanova, Valeria; Moore, Peter; Marnoch, Catherine; McGrath, Nicole
<x xml:space="preserve">Abstract</x> The New Zealand Gestational Diabetes Mellitus (GDM) Guidelines, commissioned by the Ministry of Health, contains many good points, but several recommendations are creating controversy. This opinion piece discusses an alternative approach to early pregnancy screening for diabetes. We suggest that it is reasonable to refer women with an HbA1c ≥41 mmol/mol (5.9%) for further management, rather than the recommended referral threshold of ≥50 mmol/mol (6.7%). We also suggest that, for subsequent screening for GDM at 24–28 weeks' gestation, a 75 g oral glucose tolerance test should be offered rather than a 50 g glucose challenge test.